An evaluation of usage statistics to upgrade the British Library Document Supply Service (BLDSS) introduced by the Consortium of Sri Lankan Academic Libraries (CONSAL) - Wijetunge, Pradeepa; Perera, K. K. N. L. (The Library, University of Colombo., 2020)
The Consortium of Sri Lankan Academic Libraries (CONSAL) established a Document Delivery Service through the British Library Document Supply Service (BLDSS) in the year 2017. This service was funded by the University Grants Commission (UGC) of Sri Lanka and was co-ordinated by the University of Colombo. The objective of this service was to find scholarly literature, which was not locally available, and was expected to cater to the needs of all the academics attached to the state university sector. Electronic download formats were used to disseminate the articles. Initially, a trial project was implemented by depositing 2500 GBP with the commercial document supplier- British Library. The total number of articles, which have been requested through this service from 11th of November 2017 to 25th of November 2020, was eighty-four (84). Out of them, 37 (44%) were fulfilled through the British Library; 19 (23%) articles were found via other networks and 26 (31%) of the articles were unavailable. Only six (06) state universities; Peradeniya, Jaffna, Colombo, Sabaragamuwa, Sri Jayewardenepura and Moratuwa have made article requests so far. Among them, the University of Peradeniya has made the highest number of requests (56%).The majority of the requests (69%) have been made from the field of Medicine. The article delivery statistics indicate that this service is yet to be fully utilized by the scholarly community belonging to different educational streams, attached to the state university sector. A user satisfaction survey must be conducted to gather suggestions to improve the usage of this service. As there is a considerable percentage of unavailable scholarly material in the British Library, a mechanism should be developed to utilize the existing funds to access this inaccessible content by collaborating with many commercial document suppliers similar to British Library and developing an online payment system to purchase scholarly material from direct publishers.
Keywords: Document Delivery Service, British Library, CONSAL, Usage statistics